Bioinspired MXene‐Based Piezoresistive Sensor with Two‐stage Enhancement for Motion Capture. (9th February 2023) - Wang, Shenglong; Deng, Weili; Yang, Tao; Ao, Yong; Zhang, Hongrui; Tian, Guo; Deng, Lin; Huang, Haichao; Huang, Junfeng; Lan, Boling; Yang, Weiqing
Abstract: Structured piezoresistive membranes are compelling building blocks for wearable bioelectronics. However, the poor structural compressibility of conventional microstructures leads to rapid saturation of detection range and low sensitivity of piezoresistive devices, limiting their commercial applications. Herein, a bioinspired MXene‐based piezoresistive device is reported, which can effectively boost the sensitivity while broadening the response range by architecting intermittent villus‐like microstructures. Benefitting from the two‐stage amplification effect of this intermittent architecture, the developed MXene‐based piezoresistive bioelectronics exhibit a high sensitivity of 461 kPa −1 and a broad pressure detection range of up to 311 kPa, which are about 20 and 5 times higher than that of the homogeneous microstructures, respectively. Cooperating with the deep‐learning algorithm, the designed bioelectronics can effectively capture complex human movements and precisely identify human motion with a high recognition accuracy of 99%. Evidently, this intermittent architecture of biomimetic strategy may pave a promising avenue to overcome the limitation of rapid saturation and low sensitivity in piezoresistive bioelectronics, and provide a general way to promote its large‐scale applications. Abstract : A villus‐inspired MXene‐based pressure sensor is developed for motion capture. Utilizing the two‐stage enhancement of intermittent architecture and a large‐scale fabrication process, the sensor provides an ascendant way for piezoresistive bioelectronics to overcome the limitations of rapid saturation of detection range and low sensitivity in conventional microstructure‐based sensors, thus promoting a solid advancement toward the rapid development of commercial bioelectronics.